2019
DOI: 10.1039/c9cp04692e
|View full text |Cite
|
Sign up to set email alerts
|

Origin of strong red emission in Er3+-based upconversion materials: role of intermediate states and cross relaxation

Abstract: Comprehensive NIR-to-visible upconversion luminescence mechanism in Er3+-based materials is elucidated by wavelength-dependent, power-dependent, and time-resolved photoluminescence spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…This Er 3+ doping level was chosen as a starting point for several reasons: concentrations in this range have been proposed for solar cell applications. [2,24] It has also been demonstrated that the strength of cross-relaxations is acceptable within this concentration range [25,26] and that the absorption cross-section of the particles is not limiting to the experiments. There is of course a trade-off between these two effects.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This Er 3+ doping level was chosen as a starting point for several reasons: concentrations in this range have been proposed for solar cell applications. [2,24] It has also been demonstrated that the strength of cross-relaxations is acceptable within this concentration range [25,26] and that the absorption cross-section of the particles is not limiting to the experiments. There is of course a trade-off between these two effects.…”
Section: Resultsmentioning
confidence: 88%
“…The radiative electronic transitions of the β-NaYF 4 :Er 3+ nanocrystals corresponding to distinct UC emission peaks are indicated by comparison with the literature in Figure 1b. [26,27] The luminescence emission of the β-NaYF 4 :Er 3+ NPs, from 350 to 1020 nm, in cyclohexane solution is shown in Figure 1c. The spectral data were collected for a continuous wave laser excitation with a power density of P exc = 52 W cm −2 and λ exc = 1551 nm.…”
Section: Resultsmentioning
confidence: 99%
“…There would not be enough time for the nonradiation (NR) processes, which produce the 5 I 7 state Ho 3+ for the CR processes, as they are much slower than the energy processes between RE ions do. [60,74] Most Ho 3+ ions would be simply sensitized through the two-photon excitation by Yb 3+ ions and emit green light. Thus, the influence from CR processes would be "rising-falling".…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, there is cross-relaxation between Er 3+ ion and other rare-earth ions (such as Ce 3+ , Ho 3+ , and Yb 3+ ions). [13,14,22] Therefore, we believe that this phenomenon was caused by the crossrelaxation 4 G 11/2 (Er 3+ ) + 2 F 7/2 (Yb 3+ )→ 2 F 5/2 (Yb 3+ ) + 4 F 9/2 (Er 3+ ) in Cs 2 NaEr 1−x Yb x Cl 6 perovskites. The energy level diagram is shown in Figure 2e.…”
Section: Resultsmentioning
confidence: 92%